Assisted Extraction of Hemp Oil and Its Application to Design Functional Gluten-Free Bakery Foods - Noemi Baldino; Mario F. O. Paleologo; Mariateresa Chiodo; Olga Mileti; Francesca R. Lupi; Domenico Gabriele (Molecules)
Cannabis sativa L. is known for its high-value compounds, like Cannabidiol (CBD) and Cannabidiolic Acid (CBDA). It is widely used in the pharmaceutical and food industries. Different extraction methods, like Soxhlet and maceration, are commonly employed to obtain its extracts. High temperature and long extraction time can influence the yield and the purity of the extracts, affecting the quality of the final product. This study focused on optimizing CBD oil extraction from hemp inflorescences and its incorporation into a gluten-free bakery product for functionalization. Dynamic maceration (DME), assisted by ultrasound and microwave irradiation, was used. Our study explored the impact of varying sonication times (three distinct durations) and microwave powers (three levels, applied for two different irradiation times) on the resulting extracts. HPLC analysis was performed on these extracts. Subsequently, we used hemp flour and hemp oil to bake gluten-free cupcakes, which were fortified with the extracted CBD oil. Rheological characterization was used to investigate the cupcake properties, along with stereoscopic, color and puncture analysis performed on the baked samples. The most effective extraction parameters identified were 30 s of microwave irradiation at 700 W, yielding 45.2 ± 2.0 g of CBD extract, and 15 min of sonication, which resulted in 53.2 ± 2.5 g. Subsequent rheological characterization indicated that the product exhibited mechanical properties and a temperature profile comparable to a benchmark, evidenced by a height of 4.1 ± 0.2 cm and a hardness of 1.9 ± 0.2 N. These promising values demonstrate that hemp oil and hemp flour are viable ingredients for traditional cakes and desserts, notably contributing increased nutritional value through the CBD-enriched hemp oil and the beneficial profile of hemp flour.